Correlation of Duplex Scan and Clinical Profile of Peripheral Vascular Diseases In Dmch - Abedin, Mohammad Raisul; Afzalul Haque, Abu Hasanat Muhammad; Shamsuzzaman, Sheikh Mohammad (Journal of Dhaka Medical College, 2023)
Background: Duplex ultrasound is a non-invasive evaluation of blood flow in the major arteries and veins. It provides a unique spectrum of details, including the anatomical location of the lesion, accompanied by further information about flow velocity and volume. Day by day, this investigation has become popular among physicians and surgeons to evaluate peripheral arterial disease. Objective: To determine duplex scans’ accuracy in diagnosing peripheral arterial disease and correlate it with clinical diagnosis. Materials & Methods: The cross-sectional study was conducted in the Department of General Surgery in collaboration with the Department of Radiology & Imaging, Dhaka Medical College Hospital, and Dhaka from January 2011 to December 2011. A total of 100 clinically diagnosed cases of peripheral arterial disease, irrespective of age and sex, were included in the study. However, emergency cases of peripheral arterial disease and patients of peripheral arterial disease with concomitant cerebrovascular disease or venous pathology or arterio-venous malformation were excluded from the study. Based on clinical signs and symptoms, a clinical diagnosis was made, correlated with the diagnosis made by duplex scan findings. Result: Peripheral arterial disease was mainly confined to the lower limb (85%). The right limb was involved in about two-thirds (64%) of the cases, the left limb in 31%, and both limbs in 5% of cases. More than 90% were a smoker. Pain and intermittent claudication were the universal complaints of the patients, followed by hair changes (85%), colour changes (86%) and wasting of the limb (65%). The most commonly involved arteries in the lower limb were arteria dorsalis pedis (96.6%), followed by the posterior tibial artery (84.2%), popliteal artery (60.6%), and femoral artery (21.3%). In the upper limb, the radial artery was involved in 100% of cases and the brachial artery in 86.7% of cases. Endarteritis obliterans and atherosclerosis were common clinical diagnoses (47% and 48%, respectively). Diagnosis based on duplex scan findings also demonstrated that endarteritis obliterans and atherosclerosis were common (40% and 39%, respectively), bearing consistency with clinical diagnosis. The strength of agreement between the two diagnoses was moderate (k = 0.743). Conclusion: The study concludes that there was a moderate agreement between Clinical diagnosis and duplex diagnosis, which indicates that a duplex scan can be a valuable tool to support clinical diagnosis, suggest other diagnoses, or detect other associated pathologies. J Dhaka Med Coll. 2022; 31(1) : 98-106